Relasi Perwakilan, Pemilihan dan Voting dalam Penyelenggaraan Demokrasi di Indonesia - Eko Prio Purnomo; Sumardi Sumardi (Journal of Government Insight, 2021)
This paper aims to analyze the practice of political administration in Indonesia with various models and democratic systems that are applied. Using descriptive qualitative analysis with literature review. Through comparison of Model Selection, Representative and Voting. Democracy held through election celebrations general periodicity actually becomes the foundation and umbrella for its creation development of culture and improvement of community welfare and interests general. However, the process tends to indicate that it is just a place to find form and very difficult to adjust. Between Representatives, Elections and Voting exist ideal democracy seems to be an anomaly in the realization of the quality of democracy. The implications are diverse, political parties thrive not in direct proportion to the quality of state policies, strengthening the existence of elite power without caring for common sense government administrators as state control. Finally comes the distribution of power who have no public trust.